GENE POLYMORPHISM IN ATOPIC DERMATITIS (Scientific journal of the Fergana State University, 2023)
According to the literature, 80% of children with atopic dermatitis (AtD) have a family history. At the same time, the connection with atopic diseases is more often determined on the maternal side (60-70%), less often on the paternal side (18-22%). The presence of atopic diseases in both parents increases the risk of developing AtD in a child by 60-80% [2]. With atopy in one of the parents , it decreases to 45-50% [1, 2]. 50%- the risk of spreading the disease is autosomal dominant. But at the same time, unlike vulgar ichthyosis, it was never considered such. According to the literature, 80% of children with atopic dermatitis (AtD) have a family history. At the same time, the connection with atopic diseases is more often determined on the maternal side (60-70%), less often on the paternal side (18-22%). The presence of atopic diseases in both parents increases the risk of developing AtD in a child by 60-80% [2]. With atopy in one of the parents , it decreases to 45-50% [1, 2]. 50%- the risk of spreading the disease is autosomal dominant. But at the same time, unlike vulgar ichthyosis, it was never considered such.